#TITLE_ALTERNATIVE# - HAMZAH SYAHRUDDIN (NIM 32305001) , MUHAMMAD
If the fluid flows at porous media, it generates the natural electricity resource and known as the streaming potential or the electrokinetic potential (PE). The PE phenomenon indicates that there is a relationship between the fluid flow velocities with the electricity potential. Electrokinetic potential at the sub surface of porous media due to the source of self-potential (SP) can be measured on the surface. This study investigates the fluid flow by SP method which is carried out by the fluid flow velocity quantification. Thus, SP anomaly value at the surface can be analyzed either qualitatively or quantitatively as the useful findings of the fluid flow velocity at the sub surface. The aim of this study is to develop the relationship between the fluid flow velocity at the porous media (KR) with the sub surface electrokinetic potential value using the derivation of combination Helmholtz equation and Darcy's law. The relationship between the KR and the PE is the equation which underlaies the relationship between KR and SP. The techniques which are employed to know the relationship between the KR and the SP are through the laboratory experiment, mathematics modeling, and physical modeling. From the laboratory experiment results, mathematics modeling, and physical modeling, it can be formulated that the relationship between SP and KR can be used identify the fluid flow velocity. Based on the result of physical modeling, it can be identified that the KR value from 0.017 cm/s-0.045 cm/s generates the SP anomaly from 2 mV-28 mV. The study provides two hypotheses i.e.: (1) that through laboratory experiment; the value of electrohydraulic conductivity (C) and the value of hydraulic conductivity (K) from the medium for some soil samples are affected by the grain size. The C and K value are used in the mathematics and the physical modeling. The physical modeling is used to identify the SP distribution anomaly, while mathematics modeling is used to identify the calculated SP distribution; (2) that measurable SP anomaly at the surface is the sub surface PE. The PE manifestation is a electric potential from the electric double layers (EDL) which take place between layer + and - (solid and liquid phases). The EDL electricity charges changing represents the KR as the SP anomaly source. The Differential Laplace Equation (DLE) is the equation that can be used to describe the KR and the PE distribution. These distributions are completed through the mathematics modeling and the numeric modeling. The mathematics modeling is used to transform the DLE to Integral Laplace Equation (ILE). Further more, the ILE is simplified to obtain gradient hydraulic head equation as the position. The numeric modeling is used to complete gradient hydraulic head equation. The Boundary Element Method (BEM) approach was used in the numeric calculation BEM becomes the general numeric solution of DLE. The studies show the following conclusions: firstly, laboratory experiment shows that the K value is the linier with the C value. The relation between K and C is exponential relationship. The experiment result shows that the K value from 0.01 cm/s-0.04005 cm/s generates the C value from 0.0187 mV/cm-0.081 mV/cm. Secondly based on the laboratory experiment, mathematics modeling and physical modeling, SP anomaly indicates the sum PE value in the vertical and horizontal direction. Thirdly, the analysis and synthesis of this research shows that there is a relation between the SP anomaly as the KR function and the electrode spacing (as). The benefit of this study is if the SP anomaly value of the fluid flow at the sub surface is identified, than it can be used to estimate the fluid flow velocity at the sub surface. In addition, the fluid flow pattern can be identified from the SP anomaly; which is perpendicular to the streamline with the SP contours. The fluid flow velocity estimation of SP anomaly can be carried out through the forward modeling.